2x² - 14x + 12 = 0
2x² - 2x - 12x + 12 = 0
2x(x - 1) - 12(x - 1) = 0
(2x - 12)(x - 1)
- - -
roots
2x - 12 = 0
2x - 12 + 12 = 0 + 12
2x = 12
2x / 2 = 12 / 2
x = 12 / 2
x = 6
- - - - - -
Roots
x - 1 = 0
x - 1 + 1 = 0 + 1
x = 1
- - - - - - - -
Quadratic formula
x = - b ± √b² - 4ac / 2a
x² - 14x + 12 = 0
a = 2
b = - 14
c = 12
x = - (- 14) ± √(- 14) - 4(2)(12) / 2(2)
x = 14 ± √196 - 96 / 4
x = 14 ± √100 / 4
x = 14 ± 10 / 4
- - - - - - - -
Solving for +
x = 14 + 10 / 4
x = 28 / 4
x = 6
- - - - - - -
Solving for -
x =14 - 10 / 4
x = 4 / 4
x = 1
- - - - - - - -s-
2007-04-07 09:25:30
·
answer #1
·
answered by SAMUEL D 7
·
0⤊
0⤋
Factor out the 2, so you get 2(x^2-7x+6)=0, which then becomes 2(x-6)(x-1)=0. Solve each piece: x-6=0 and x-1=0 So, x=1 and x=6 are the two answers.
2007-04-07 09:03:05
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
First, you can divide the whole equation by 2
x^2 - 7x + 6 = 0
Then you have a few options.
Factor
(x-1)(x-6) = 0
x = 1 or 6
Use quadratic formula
x = (-b+/-sqrt(b^2 - 4 x a x c))/2a
x = (7 +/-sqrt(49 - 4 x (1) x (6))/2
x = 7/2 + 5/2 or 7/2 - 5/2
x = 1 or 6
2007-04-07 09:10:58
·
answer #3
·
answered by actaha 2
·
0⤊
0⤋
x=1 and x=6
2007-04-07 09:01:37
·
answer #4
·
answered by ♥ ©o©oA ♥ 4
·
0⤊
0⤋
2X^2-14x+12=0
solution goes this way....
2X^2-14x+12=0
2X^2-12x-2X+12=0(here the two factors are 12 nd 2)
2X(X-6) -2(X-6)=0
(x-6) (2X-2)
so the value of X is 6 and 1
as X-6=0 gives X=6 nd 2X-2=0 which gives X= 1
2007-04-07 09:07:59
·
answer #5
·
answered by saranya 1
·
0⤊
0⤋
If you want to, you can first simplify it by removing the common factor 2. you then get:
x^2 - 7x + 6 = 0
Either factor it as (x-6)(x-1) = 0
and set each term to 0
or use the quadratic formula (-b +/- sqrt(b^2-4ac)/2a
2007-04-07 09:02:50
·
answer #6
·
answered by astatine 5
·
0⤊
0⤋
2x^2-14x+12=0
divide by 2
x^2-7x+6 =0
(x-6)(x-1)=0
x = 6, 1
2007-04-07 09:01:35
·
answer #7
·
answered by jaybee 4
·
0⤊
0⤋
divide by 2
x^2 -7x +6 =0
factor
(x-1)(x-6) = 0
x-1 = 0 so x = 1
x-6 = 0 so x = 6
the answer is x=1 and x=6
2007-04-07 09:02:24
·
answer #8
·
answered by bignose68 4
·
0⤊
0⤋
2(x^2-x)-12(x+1)=0
2(x^2-x)=12(x+1)
(x^2-x)=6(x+1)
x^2-x=6x+6
x^2-7x-6=0
x^2-x-6x-6=0
x(x-1)- 6(x-1)=0
(x-1)(x-6)=0
x=1 or x=6
2007-04-07 09:10:08
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋
x² - 7x + 6 = 0
(x-6)(x-1) = 0
x = 1, or 6
2007-04-07 09:01:04
·
answer #10
·
answered by Anonymous
·
0⤊
0⤋